2015
DOI: 10.1088/1751-8113/48/35/355203
|View full text |Cite
|
Sign up to set email alerts
|

Deformed integrableσ-models, classicalR-matrices and classical exchange algebra on Drinfel’d doubles

Abstract: We describe a unifying framework for the systematic construction of integrable deformations of integrable σ-models within the Hamiltonian formalism. It applies equally to both the 'Yang-Baxter' type as well as 'gauged WZW' type deformations which were considered recently in the literature. As a byproduct, these two families of integrable deformations are shown to be Poisson-Lie T -dual of one another.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
213
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(219 citation statements)
references
References 77 publications
5
213
0
1
Order By: Relevance
“…Indeed, the computation of the corresponding RG flow equations using gravitational methods was performed in [2,3] and is in agreement with results from field theoretical methods [8][9][10]. Furthermore, it was shown that these models, named generically as λ-deformed, can be embedded in specific cases of low dimensionality to supergravity [11][12][13][14][15], while their relation to η-deformations for group and coset spaces introduced in [16][17][18] and [19][20][21] respectively, via Poisson-Lie T-duality [22] and appropriate analytic continuations, was uncovered in [23][24][25][26][27]. More recently, the computation of the all-loop correlators for the…”
Section: Jhep03(2017)083supporting
confidence: 70%
See 1 more Smart Citation
“…Indeed, the computation of the corresponding RG flow equations using gravitational methods was performed in [2,3] and is in agreement with results from field theoretical methods [8][9][10]. Furthermore, it was shown that these models, named generically as λ-deformed, can be embedded in specific cases of low dimensionality to supergravity [11][12][13][14][15], while their relation to η-deformations for group and coset spaces introduced in [16][17][18] and [19][20][21] respectively, via Poisson-Lie T-duality [22] and appropriate analytic continuations, was uncovered in [23][24][25][26][27]. More recently, the computation of the all-loop correlators for the…”
Section: Jhep03(2017)083supporting
confidence: 70%
“…It was shown in [23][24][25][26][27] that, the λ-and η-deformations are related via Poisson-Lie T-duality and appropriate analytic continuations. Our construction and results suggest that there likely exist new integrable σ-models of the η-type to be constructed.…”
Section: Jhep03(2017)083mentioning
confidence: 99%
“…A duality of this type was considered in [33], which relates an η s deformation (the superscript denoting it is based on a split solution of the modified classical Yang-Baxter equation) to the corresponding λ deformation. In both cases the duality is with respect to the full symmetry group of the undeformed model.…”
Section: Jhep11(2017)014mentioning
confidence: 99%
“…Starting from the corresponding model on the Drinfel'd double (2.20) this allows us to investigate in which subgroups of G the η deformed model can be Poisson-Lie dualised and construct the corresponding backgrounds. Our starting point for the construction of the η deformed model will be the compact simple Lie group G, with Lie algebra g = Lie(G), and the complex Drinfel'd double D ≡ G C , with Lie algebra d ≡ g C = Lie(D) [10,12,33,41].…”
Section: The η and λ * Deformed Modelsmentioning
confidence: 99%
“…In the latter case, there are a lot of classical r-matrices satisfying the cybe and some of them are associated with well-known gravitational backgrounds, such as Lunin-Maldacena-Frolov backgrounds [39,40], gravity duals for non-commutative gauge theories [41,42], Schrödinger spacetimes [43][44][45][46][47] and gravity duals for dipole theories [48][49][50][51][52], as shown in a series of works [53][54][55][56][57]. Very recently, the reality of the classical action has been revisited in [58] and a unified picture of deformed integrable sigma models has been provided in [59].…”
Section: Jhep10(2015)185mentioning
confidence: 99%